If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 2) + -16 = 18 + 1 Reorder the terms: -7(2 + x) + -16 = 18 + 1 (2 * -7 + x * -7) + -16 = 18 + 1 (-14 + -7x) + -16 = 18 + 1 Reorder the terms: -14 + -16 + -7x = 18 + 1 Combine like terms: -14 + -16 = -30 -30 + -7x = 18 + 1 Combine like terms: 18 + 1 = 19 -30 + -7x = 19 Solving -30 + -7x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -7x = 19 + 30 Combine like terms: -30 + 30 = 0 0 + -7x = 19 + 30 -7x = 19 + 30 Combine like terms: 19 + 30 = 49 -7x = 49 Divide each side by '-7'. x = -7 Simplifying x = -7
| X+(2x-3)=72 | | 3+(15-1)(-4/3) | | 5y-2=29-4y | | 6=6+y | | 5(-3+7x)=-330 | | x+x*0.09=1000 | | 2(0.3r+1)=24 | | x-1/3=4/3 | | 5x+1=43-2x | | 2x^2+5x+6=x^2 | | 21x-16y=120 | | 10x-42+17x=13+14 | | .0855t^2-.916t+1.737=0 | | 8+2t-2=7t+8-4t | | 3(X+2)(X+2)+16(X+2)+5= | | 3+(5x-6/4) | | 3mx-9y=2(m+2b) | | x-7=144 | | 4s^2+16s-as-4a= | | 2/3(3/5) | | (5/6)t+4=(1/6)t-2 | | 13x+3x-5=27 | | .0825t^2-.886t+1.752=0 | | 5x-15=x+25 | | -x^2+11=0 | | -8+x/8=-12 | | 6(6x+5)=-390 | | (10)+c^3/3=c^3/(3)+10 | | 6x+3=4x+7 | | 3x^2+5x+343=0 | | 11x-2(4x-6)=18 | | 2-20q-3q+12=5+4q+15 |